Reinforcing Lecturer Readiness to Change by Increasing Psychological Capital and Engagement - Lista Meria; Corry Yohana; Unggul Purwohedi; Saukani; Dwi Apriliasari (Aptisi Transactions On Technopreneurship (ATT), 2023)
Organizational change demands effective management, with the preparedness of human resources playing a pivotal role in achieving success. This study explores the interplay of psychological capital, work engagement, and entrepreneurial mindsets (both intrapreneurial and entrepreneurial) as predictors of lecturers' readiness for change. Conducted with 331 lecturers from private universities in Indonesia (Esa Unggul, Jakarta state university and Muhammadiyah Pringsewu, the research employs Structural Equation Modeling with Partial Least Squares (SEM PLS) for data analysis. The findings underscore the substantial influence of psychological capital and work engagement in enhancing lecturer readiness for change. Additionally, work engagement emerges as a critical mediator in the relationship between psychological capital and readiness for change. Notably, the study contributes to our understanding by delving into both intrapreneurial and entrepreneurial dimensions of entrepreneurial mindsets, offering a nuanced perspective on the factors shaping educator readiness for change. The research contributes theoretically by shedding light on the multifaceted roles of entrepreneurial mindsets in strengthening readiness for change, addressing a gap in the existing literature. Practical insights advocate for the cultivation of diverse entrepreneurial mindsets among educators to successfully navigate organizational change. This study establishes a foundation for future research in this evolving domain, emphasizing the significance of entrepreneurial approaches in preparing lecturers for the challenges posed by organizational change.